2018
DOI: 10.1177/1069072718780447
|View full text |Cite
|
Sign up to set email alerts
|

Five-Factor Personality Traits and RIASEC Interest Types: A Multivariate Meta-Analysis

Abstract: Determining the relationships between five-factor model (FFM) personality dimensions and Realistic, Investigative, Artistic, Social, Enterprising, and Conventional (RIASEC) types is important for counselors and clients during the career choice process. There have been mixed findings regarding this relationship, necessitating this research. The purpose of this study was to determine the relationship between the FFM and RIASEC interest types employing a multivariate meta-regression meta-analysis. Thirty-four stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 79 publications
3
23
0
8
Order By: Relevance
“…We expect to find a factorial structure of EIAPsi similar to the one found in the Brazilian version, formed by 11 factors/ areas of Psychology (Ambiel & Martins, 2016, 2019; as well as positive correlations between personality traits Openness, Extroversion, Conscientiousness and Agreeableness and areas of interest measured by EIAPsi (Ambiel, Noronha, & Nunes, 2012;Bueno et al, 2004;Bullock & Reardon, 2008;Hurtado Rúa et al, 2019;Wille & De Fruyt, 2014); finally, the Neuroticism personality trait is expected to correlate negatively with the areas of interest measured by the EIAPsi (Bueno et al, 2004;Bullock & Reardon, 2008;Hurtado Rúa et al, 2019;Wille & De Fruyt, 2014).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We expect to find a factorial structure of EIAPsi similar to the one found in the Brazilian version, formed by 11 factors/ areas of Psychology (Ambiel & Martins, 2016, 2019; as well as positive correlations between personality traits Openness, Extroversion, Conscientiousness and Agreeableness and areas of interest measured by EIAPsi (Ambiel, Noronha, & Nunes, 2012;Bueno et al, 2004;Bullock & Reardon, 2008;Hurtado Rúa et al, 2019;Wille & De Fruyt, 2014); finally, the Neuroticism personality trait is expected to correlate negatively with the areas of interest measured by the EIAPsi (Bueno et al, 2004;Bullock & Reardon, 2008;Hurtado Rúa et al, 2019;Wille & De Fruyt, 2014).…”
mentioning
confidence: 81%
“…This relationship was verified in the study by Shimada, Melo-Silva and Taveira (2016). In turn, the meta-analysis carried out by Hurtado Rúa, Stead and Poklar (2019), indicated that the Big Five dimensions most related to RIASEC's interests were Opening and Extroversion. In view of this issue, it becomes necessary to discuss the interface between professional interests, personality and areas of Psychology, considering the need to understand the existing variables and the possibility of offering training that can manage the demands that arise during the process, due to the choice among the specialties of Psychology.…”
mentioning
confidence: 99%
“…Finally, there is evidence indicating that vocational interests share some common variance with other individual difference variables, such as the Big Five personality constructs (Armstrong & Anthoney, 2009; Barrick, Mount, & Gupta, 2003; Larson, Rottinghaus, & Borgen, 2002). For example, Artistic interests are positively associated with openness; Enterprising interests with extraversion; Investigative interests with openness; and Social interests with both extraversion and agreeableness (Larson et al, 2002; Hurtado Rúa, Stead, & Poklar, 2019). Conscientiousness, agreeableness, extraversion, and neuroticism have each been linked to different types (FIW, WIF) and dimensions (strain‐, time‐, and behavior‐based) of WFC (Allen et al, 2012).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…They are attracted to work in jobs such as teaching, counseling, and other community services. Social interests are strongly related to Extraversion and moderately related to Agreeableness (Hurtado Rúa et al, 2019). Individuals with Social interests are more likely to find a partner and have children (Stoll et al, 2017).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Holland mendalilkan bahwa minat vokasional adalah ekspresi kepribadian seseorang, dan bahwa kepentingan kejuruan dapat dikonseptualisasikan kedalam enam tipologi (RIASEC) yang diantaranya Realistis, Investigasi, Artistik, Sosial, Enterprising, dan Konvensional (Leung, 2008). John Holland (RIASEC) menyatakan bahwa dalam memilih karir, orang lebih suka pekerjaan dimana mereka bisa berada di sekitar orang lain yang memiliki minat dan tipe kepribadian yang seperti mereka, lebih lanjut mereka juga akan memilih lingkungan yang dapat memfasilitasi mereka dalam mengeksprsikan diri dan kemampuannya (Hurtado Rúa, Stead, & Poklar, 2019;McKay & Tokar, 2012.…”
Section: Kajian Pustakaunclassified